A multi‐center, observational study shows high proportion of Australian rheumatoid arthritis patients have inadequate disease control. (26th October 2013) - Littlejohn, Geoffrey; Roberts, Lynden; Arnold, Mark; Bird, Paul; Burnet, Simon; de Jager, Julien; Griffiths, Hedley; Nicholls, Dave; Scott, James; Zochling, Jane; Tymms, Kathleen E.
Abstract: Objectives: To evaluate the disease activity and current pharmacological interventions used to achieve remission in rheumatoid arthritis (RA) patients in Australia. Methods: Rheumatoid arthritis patients treated in participating Australian clinics were included in the study. Patient demographics, disease onset, medications and disease measures were analyzed. Data, de‐identified to the patient, clinic and clinician were captured using an electronic clinical management program. The disease activity score (DAS28) was used to classify patients into the disease activity states of remission, low disease activity (LDA), moderate disease activity (MDA) and high disease activity (HDA). Choice of therapy was at the discretion of the treating clinician. Results: A total of 5686 patients, 72.9% female, 26.9% male, with mean age 61.1 (SD 13.6) years and mean disease duration of 11.5 (SD 10.5) years were analyzed. DAS28 ESR (erythrocyte sedimentation rate) scores were recorded for 2973 patients, with 41.6% in remission, 18.6% LDA, 31.6% MDA and 8.2% HDA. Of those in remission, 17% received a biological disease modifying anti‐rheumatic drug (bDMARD), 73% methotrexate (MTX), 19% leflunomide (LEF) and 28% prednisolone. Of the patients with MDA, 20% received a bDMARD, 76% MTX, 24% LEF and 39% prednisolone. Of the patients in HDA, 27% received a bDMARD, 78% MTX, 31% LEF and 60% with prednisolone. Conclusions: Cross‐sectional assessment of this large cohort of Australian RA patients found a large proportion remain in moderate or high disease activity; suggesting a considerable evidence–practice gap. Improvement in disease control in this group may reduce future health burdens.